Effect of Mixed Manure and Inorganic Fertilizer on Phosphorus Adsorption and Desorption Characteristics of Vertisols in Haramaya District, Eastern Ethiopia - Dejene Teressa; Kibebew Kibret; Nigussie Dechasa; Lemma Wogi (The Scientific World Journal)
Applying inorganic phosphorus fertilizer is less effective in increasing crop yields in tropical soils due to precipitation and adsorption reactions. However, research suggests that partial substitution of organic and inorganic fertilizers has shown to improve the efficiency of applied phosphorus fertilizer by reducing its adsorption and enhancing desorption due to their synergistic effects. This study aimed to investigate the impact of treating the soil with mixed manure (MM) rates and blended nitrogen, phosphorus, sulfur, and boron (NPSB) fertilizer on the soil’s phosphorus adsorption and desorption characteristics. Results showed increased adsorbed phosphorus in all treatments, with increased added phosphorus (P) concentration from 100 to 500 mg kg−1. However, the efficiency of adsorbed P decreased significantly as added P concentration rates increased from 100 to 400 mg·kg−1 in all treatments and then decreased as the added P concentration advanced to 500 mg·kg−1. Moreover, in all treatments that received combined applications of MM and blended NPSB, both quantity and percentage of desorbed P showed a significant increase. The Freundlich adsorption coefficient and constant were also significantly reduced because of the combined application of MM and blended NPSB, compared to the control and their sole applications. Overall, the soil treated with a combined application of 15 t·ha−1 of MM with 100 kg·ha−1 of blended NPSB showed the highest reduction in the efficiency of adsorbed P, percentage of desorbed P, Freundlich adsorption capacity, and intensity by 8%, 37.5%, 60%, and 58%, respectively, as compared to the control. These findings indicate that the combined application of MM and blended NPSB can improve the P availability and uptake by maize by reducing its adsorption while increasing desorption characteristics. Finally, this experiment recommends further research on the long-term effects of MM and blended NPSB on P adsorption and desorption characteristics of vertisols.